Glossifungites gingrasi n. isp., a probable subaqueous insect domicile from the Cretaceous Ferron Sandstone, Utah. (May 2021) - King, M. Ryan; La Croix, Andrew D.; Gates, Terry A.; Anderson, Paul B.; Zanno, Lindsay E.
Abstract: A new ichnospecies, Glossifungites gingrasi n. isp., is described from multiple locations in basal sand-filled coastal plain distributary channels of the Turonian (Upper Cretaceous) Ferron Sandstone (central Utah). Glossifungites gingrasi n. isp. is attributed to the ichnogenus Glossifungites based on the presence of scratch imprints, passive fill, and a tongue-shaped structure, yet the new ichnospecies is distinct because it displays transverse bioglyphs that run perpendicular to the planiform structure, which contrasts to the axis parallel bioglyphs present in the ichnospecies G . saxicava . The transverse arrangement of ornamentation exhibited by G . gingrasi n. isp. is observed in modern subaqueous insect burrows produced by mayfly and chironomid larvae, and constitutes a way to differentiate insect-generated burrows from structures produced by crustaceans that are known to create other Glossifungites ichnospecies. Differentiating insect- from crustacean-generated burrows is significant because it provides a way to distinguish bioturbation by marine-recruited fauna from that produced by freshwater fauna in the rock record, making G . gingrasi n. isp. a valuable ichnological tool for paleoenvironmental and stratigraphic interpretation. While G . gingrasi n. isp. may represent a burrow created by a variety of filter-feeding subaqueous insects, the large size of G . gingrasi n. isp. in the Ferron Sandstone suggests that the largest specimens are probable mayfly burrows and supports the assertion that burrowing mayflies (e.g., Polymitarcyidae and Ephemeridae) adapted to domicile filter-feeding during or prior to the Turonian. UUID: http://zoobank.org/a033b22f-bf09-481a-975e-3a1b096154cc